HUBUNGAN PEMBELAJARAN LOMPAT KIJANG TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK SISWA - Moh Cholili; Khoirul Anwar; Fajar Hidayatullah (LPPM Universitas Negeri Medan, 2022)
Physical education can influence students' attitudes through athletic sports activities by exploring the potential of students to excel. One of the athletic materials studied in physical education is learning the squat style long jump. And the antelope jump learning method is a type of plyometrics learning that is carried out using one leg which students do alternately and repeatedly. This study aims to determine the effect of long jump learning outcomes with the squat style by providing treatment in the form of a deer jump learning method for male students of class VII MTs. Nurul Karomah. This research was conducted in MTs. Nurul Karamah with 25 students. The method used in this study is quasi-experimental. Based on the results of the research, the normality test is 0.200, which means >0.05 is normally distributed, the homogeneity test results obtained a value of 0.834, which means <0.05 is declared homogeneous, while the t-test results show that the significant value is 0.000, meaning less than 0.05, then Ho is rejected. This shows that there is a significant difference between before and after giving learning to students.